Social Work and the Mass Media: Perspectives and Possibilities of Encounter - Muriel-Saiz, Mercedes; Martín-Estalayo, Maribel (Prospectiva. Revista de Trabajo Social e Intervención Social, 2020)
The following article is a review of the scientific and professional literature that identifies the relationship between mass media and Social Work. Although it is a field that is not very developed, international and national research coincides in recognizing the social impact and the power that the media exerts in the construction and projection of Social Work as a profession and, at the same time, it is sometimes observed how this image is violated due to lack of knowledge or sensitivity. A central idea that runs through the whole argument is that maintaining distance and an attitude of mutual ignorance is not only a question of image but has significant repercussions on the link that is established between the social worker and the subject of intervention in an institutional context. Working towards an image more in line with reality is an urgent educational task and a duty towards the profession and the public.